Water quality policy and management in Asia - Tortajada, Cecilia (London : Routledge, 2013)
policy and management, it is important to acknowledge the multiplicity of interrelated and often conflicting events, issues, actors and interests, both within and outside the water sector that impact them. This complexity, alongside institutional inability for systematic and coordinated collaboration, are potent reasons as to why, in the second decade of the 21st century, formulation and implementation of efficient water quality management policies benefitting humankind and the environment have still not been achieved. The book was originally published as a special issue of the International Journal of Water Resources Development.
Fakulti Sains Bumi.
Includes bibliographic references and index.
Keywords: Water quality management -- Asia; Water quality -- Asia; Water use -- Asia; Water-supply -- Management -- Asia